Airway epithelial stem cell renewal and differentiation: overcoming challenging steps towards clinical-grade tissue engineering - Davide Adamo; Vincenzo Giuseppe Genna; Giulia Galaverni; Chiara Chiavelli; Alessia Merra; Fabio Lepore; Federica Boraldi; Daniela Quaglino; Jessica Evangelista; Filippo Lococo; Graziella Pellegrini (Stem Cell Research & Therapy)
Abstract Background Despite their life-saving potential, tissue engineering approaches for the treatment of extensive tracheal and bronchial defects still face significant limitations. A major challenge is the inability to regenerate a functional airway epithelium containing the appropriate amount of stem cells required for long-term tissue renewal following transplantation of the bioengineered graft. In this scenario, extensive cell culture characterization, validation assays and quality controls are needed to guide each step of the regeneration process. Methods Stem cell depletion is often due to suboptimal culture conditions, therefore we tested the ability of a clinical-grade culture system to support the safe and efficient in vitro expansion and differentiation of primary human tracheal and bronchial epithelial cells. Single-cell clonal analysis was used to unravel the heterogeneity of airway basal cells and to understand tissue-specific regeneration and differentiation mechanisms. Functional assays were used to investigate the wound healing ability and tightness of the regenerated epithelium under the selected culture conditions. Results Primary tracheobronchial epithelial cells showed an impressive proliferative potential, allowing the regeneration of a mature and functional epithelium without immortalisation events. Analysis at the single cell level allowed the identification of the subpopulation of basal cells endowed with in vitro self-renewal, distinguishing them from transient amplifying cells. This approach has further defined the hierarchy of cellular differentiation and its correlation with regenerative and differentiation potential. Conclusions Our results show that primary airway epithelial cell cultures can maintain stem cells together with their differentiation lineages in vitro. Airway cells can be safely and effectively used in autologous tissue engineering approaches when cultured under appropriate and well-standardised conditions. In addition to the validation assays proposed for the development of new advanced therapy products, this study outlines possible quality controls to enhance therapeutic success and maximise patient safety in future clinical applications.